Effect of topography on rainfall during southwest monsoon (with special reference to spatial distribution) - Nishanthi, D.D. (My University, 2004)
Thisresearch advances the study of effect of topography on Southwest rainfall in Sri Lanka.This dissertation begins with an introduction about the climate of Sri Lanka. Then, the general features and seasonal changes of the climate are discussed. The Southwestmonsoon and its synoptical features are also taken place. Considering the data at the selected rainfall reporting stations located with in a band from west to east, the rainfall variations with the topography are discussed. The maximum rainfall is observed at the region, which is located about 24 km away from the mountain crest towards west coastline in Southwest monsoon period. This is due to the effect of topography